Cuidados de enfermería al paciente con trauma de tórax (2000)
ABSTRACT: Trauma of the thorax, a frequent cause of morbility and mortality in Colombia, offers a challenge to nursing professionals in terms of care; because the thoracic cavity contains organs whose adecuate function is vital to maintaining life. The signs and symptoms which are produced are varied and the clinical findings become very complex. This article seeks to describe the principal injuries and commonly occurring alterations in the adult population, the essential and most frequent nursing diagnoses, standardized guide for nursing care in case of thoracic trauma and the results they should expect after appropriate intervention. The nursing diagnoses were made according to be the methods of nursing procedure.